Ministry of Communications and Information Technolog Decree No. 467 of the year 2024 Amending the Executive Regulations of law No. 15 of the year 2004 Regulating Electronic Signature and Establishing the Information Technology Industry Development Agency = قرار وزير الاتصالات وتكنولوجيا المعلومات رقم 467 لسنة2024 بتعديل للائحة التنفيذية للقانون رقم 15 لسنة 2004 بتنظيم التوقيع الالكتروني وبإنشاء هيئة تنمية صناعة تكنولوجيا المعلومات / Prime Minister. - Egypt. Prime Minister. (2025)
Chapter1: Definitions and general provisions -- Chapter2: Reliable electronic transactions and activities of information technology -- Chapter3: trust services license procedures -- Chapter: General procedural provisions